Europejska klasyfikacja regionów a fundusze strukturalne - Pancer-Cybulska, Ewa; Szostak, Ewa (European Regional Classification and Structural Funds, 2009)
The paper shows the essence of NUTS classification and its role as the foundation of structural funds distribution. An appropriate delimitation of NUTS 2 regions could contribute to an increase in participation of regions and countries in structural funds. The paper also indicates examples of states using such methods as a model to implement in Poland which should divide Mazowieckie voivodship into two regions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 769-778